TINJAUAN YURIDIS PEMBUKTIAN PENCEMARAN NAMA BAIK MENURUT HUKUM PIDANA - Aditya Fattahillah Sigit (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACT Defamation is the act of defaming someone's good name by stating something, either verbally or in writing. The issue of slander and defamation, especially in criminal law, has been under the spotlight, both in its formulation and in practice. Defamation consists of two elements, that is the act of defamation and the object of defamation in the form of tarnished a person's good name. Defamation can be defined as an act of someone that results in tarnishing the good name of another person or an object is insulted.This study uses a normative juridical approach,  legal research which is carried out by examining library materials or secondary data as the basic material to be studied by conducting a search of the regulations and literature related to the problem under study, namely against defamation according to criminal law. .Research results and discussion review of the Criminal Law of defamation is to use the existing laws and regulations in the criminal code and the ITE Law.. Legal analysis of defamation Taking the example of the case against Baiq Nuril through the Supreme Court Decision No.574 / K / PID.SUS / 2018 and the Judge's Consideration in Deciding the case.Keywords: Defamation. Proof